Pengetahuan tentang Anak Berkebutuhan Khusus, Empati dan Dukungan Sosial Orangtua - Widji Lestari (JCE (Journal of Childhood Education), 2019)
Special Needs child (ABK) is the child that is unique in the type and characteristics, which distinguish from normal children in general.This study aims to determine the relationship between knowledge about special need child, empathy and parents social support. The population in this study were parents who have not a special need children but their children have the same school with a special need child. The research sample was 50 parents, using purposive random sampling technique. Results of research by Spearman Correlation analysis: 1) TheÂ  relationship between knowledge with social support obtained by 0,505 with significant level of p = 0.05. 2) The relationship between empathy and social support obtained for 0,970 with a significance level of p = 0.05. 3) This study shows that there is no relationship between knowledge about special need child,, empathy and parents social support